2019
DOI: 10.1002/adma.201807160
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Domain Architecture in 2D α‐Mo2C via Polarized Raman Spectroscopy

Abstract: MXenes are emerging 2D materials with intriguing properties such as excellent stability and high conductivity. Here, a systematic study on the Raman spectra of 2D α‐Mo2C (molybdenum carbide), a promising member in MXene family, is conducted. Six experimentally observed Raman modes from ultrathin α‐Mo2C crystal are first assigned with the assistance of phonon dispersion calculated from density functional theory. Angle‐resolved polarized Raman spectroscopy indicates the anisotropy of α‐Mo2C in the b–c plane. Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 92 publications
5
35
0
Order By: Relevance
“…The spectrum from point C in Figure 6A verifies the growth of graphene on the Cu as well, consistent with the above optical microscope results obtained by oxidation studies. In addition, we observed that some Mo 2 C crystals fell off during the transfer process, leaving behind regular shaped edge traces (B), as presented before in Ref [19]. Raman signals collected from this region (B) shows the absence of graphene underneath the Mo 2 C crystal.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The spectrum from point C in Figure 6A verifies the growth of graphene on the Cu as well, consistent with the above optical microscope results obtained by oxidation studies. In addition, we observed that some Mo 2 C crystals fell off during the transfer process, leaving behind regular shaped edge traces (B), as presented before in Ref [19]. Raman signals collected from this region (B) shows the absence of graphene underneath the Mo 2 C crystal.…”
Section: Resultssupporting
confidence: 72%
“…CVD has been a promising technique to achieve large area and high quality thin layers of Mo 2 C 3,13,22,[14][15][16][17][18][19][20][21] . In this method, Cu foil is placed on a Mo substrate and heated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CVD grown molybdenum carbide (α-Mo 2 C structure) on copper foil has been reported. [206,207] On where, the deposition of methane vapor onto a bilayer substrate of copper foil sitting on a molybdenum foil resulted in a α-Mo 2 C structure. In this process, particularly same size of Cu and Mo foils (≈1 × 1 cm 2 of each) are first placed in the center of a 1 in.…”
Section: Synthesis Of Mxene and 2d Organic Materials Brief Overviewmentioning
confidence: 99%
“…The thickness collected at the same position decreases to 2.6 nm, indicating there is~0.4-nm-thick amorphous carbon film on the Mo-C films after the carbonization process. It is worth noting that this two-step deposition Raman spectroscopy is a powerful tool to probe the structural characteristics and properties of nanostructure materials, and it is sensitive to the vibration of different chemical bonds [25,26]. The Raman spectra of Mo-C films with different thicknesses are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%